Tradisi Mitong Dedinan dalam Perkawinan di Desa Aengtontong Sumenep Madura Perspektif Maqashid Syariah - Ahmad Fauzul Adhim; Mif Rohim Noyo Syarkun; Wulida Ainur Rofiq (Program Studi Hukum Keluarga Islam (Ahwal Syakhshiyyah), Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2023)
This study aims to determine the methods and implementation of mitong dedinan in marriages of the people of Aengtongtong Village, the maqasid al-shariah view of the mitong dedinan tradition, and the results of marriages based on the mitong dedinan tradition. This study uses a qualitative research approach using an anthropological approach, namely to study behavior that has occurred repeatedly and is continuously carried out which is studied through the perspective of maqashid al-shariah. This aims to find out more deeply and obtain data and information about this tradition which is still being carried out today. Based on this research, it was found that the people of Aengtongtong village can be sure that when they are going to carry out a marriage, beforehand they will go to the dukun manten with the aim that they will have an auspicious day to carry out the marriage. From the analysis conducted by the author, there are three factors underlying the practice of dedinan namely, 1) safety, 2) psychological, 3) preservation of tradition. In the perspective of maqashid al-shariah, marriage rites are included in the maslahah tahsiniyat (tertiary) category. This tradition contains the value of the request as well as the results of marriage from this tradition, the majority of the people do not experience separation (divorce).